A current collector, a preparation method thereof, a negative electrode sheet and a lithium ion battery
Patent Information
- Application Number
- CN202611063785.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-23
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology and relates to a current collector and its preparation method, a negative electrode sheet, and a lithium-ion battery. Background Technology
[0002] With the increasing demands for energy density in lithium-ion batteries from electric vehicles and energy storage, silicon-based anode materials have become the next-generation alternative to traditional graphite anodes due to their extremely high theoretical specific capacity. For example, silicon-carbon anode materials have a theoretical specific capacity of approximately 4200 mAh / g. However, silicon materials undergo approximately 300% volume expansion and contraction during charge and discharge, leading to the pulverization of active material particles, failure of electrical contact with the current collector, and continuous damage and reconstruction of the solid electrolyte interphase (SEI). These problems are the fundamental reasons for the rapid capacity decay and short cycle life of silicon-carbon anodes.
[0003] Currently, the industry commonly uses ultra-thin composite copper foil as a current collector to reduce weight and buffer stress. Its typical structure is a "polymer base film (such as PET) + two extremely thin electrolytic copper layers." Although this "sandwich" structure improves flexibility to some extent, the bonding between its smooth copper surface and the silicon-based anode coating mainly relies on the physical adsorption of the binder, resulting in weak adhesion and high interfacial impedance. Under long-term cyclic stress, the coating is highly susceptible to peeling, leading to battery failure.
[0004] To address interface issues, existing technologies primarily focus on the binder system or the coating of the active material surface, such as developing highly elastic binders or constructing buffer layers. However, these methods do not fundamentally alter the two-dimensional contact mode between the current collector and the active layer, resulting in limited improvement and potentially introducing other side effects, such as reduced energy density and increased process complexity.
[0005] Therefore, there is an urgent need for an innovative solution that can actively enhance the bonding force with the silicon-based active layer, buffer volume expansion stress, and maintain excellent conductivity, starting from the current collector's body structure. Summary of the Invention
[0006] To address the aforementioned technical problems in existing technologies, the present invention aims to provide a current collector and its preparation method, a negative electrode sheet, and a lithium-ion battery. The present invention solves the defects of existing composite copper foil and silicon-based negative electrode interfaces, such as weak bonding, poor cycle stability, and limited process improvement effects.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a current collector, comprising:
[0009] Polymer-based film;
[0010] A copper layer is formed on at least one side surface of the polymer-based film;
[0011] A three-dimensional porous dendritic copper interface layer is formed on the surface of the copper layer.
[0012] In the current collector of this invention, the polymer base film provides basic support and excellent flexibility for the copper layer, making it adaptable to the winding and rolling processes of lithium-ion batteries. The copper layer provides good electron transport for the current collector. The dendritic structure in the three-dimensional porous dendritic copper interface layer is like countless "micro-hooks" embedded in the negative electrode active layer, transforming the traditional surface-to-surface contact into a three-dimensional interlocking connection, which can increase the bonding strength between the current collector and the silicon-based active layer; the pores between the dendrites can effectively absorb the volume expansion stress of the negative electrode active material, reduce the generation of cracks in the negative electrode active layer, and improve cycle performance; the three-dimensional porous dendritic copper interface layer has a huge specific surface area, which can significantly reduce the interfacial charge transfer impedance, which is beneficial to high-rate charge and discharge performance.
[0013] Preferably, the average porosity of the three-dimensional porous dendritic copper interface layer is 50% to 75%, for example, it can be 50%, 52%, 55%, 57%, 58%, 60%, 63%, 65%, 70%, or 75%. If the average porosity is less than 50%, the effect of the pores in the three-dimensional porous dendritic copper interface layer in absorbing the volume expansion of silicon-based materials will be insignificant; if the average porosity is greater than 75%, the mechanical strength of the copper skeleton will decrease, making it prone to collapse during electrode fabrication or cycling. Further, the porosity is preferably 55% to 65%.
[0014] Preferably, the three-dimensional porous dendritic copper interface layer includes a multi-level structure composed of dendritic copper crystals. The dendritic copper crystals include a dendritic trunk and dendritic branches growing on the dendritic trunk. The average diameter of the dendritic trunk is 100 nm to 500 nm, the length of the dendritic branches is 1 μm to 5 μm, and the angle between the dendritic trunk and the dendritic branches is 30° to 60°. For example, the average diameter of the dendritic trunk can be 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, or 500 nm, etc.; the length of the dendritic branches can be 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, or 5 μm, etc.; and the angle between the dendritic trunk and the dendritic branches can be, for example, 30°, 35°, 40°, 45°, 50°, 55°, or 60°, etc.
[0015] The multi-level structure enables the three-dimensional porous dendritic copper interface layer to provide both mechanical anchoring and stress buffering functions. The dendritic structure can be embedded in the silicon-based active layer to form a three-dimensional interlock, while ensuring the existence of pores, which can absorb the volume expansion of silicon-based materials.
[0016] Preferably, the average thickness of the three-dimensional porous dendritic copper interface layer is 1 μm to 10 μm, for example, it can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm, etc. Preferably, it is 2 μm to 6 μm. If the average thickness of the three-dimensional porous dendritic copper interface layer is too small, the effect of improving the bonding force between the current collector and the negative electrode active layer will be limited; if the average thickness of the three-dimensional porous dendritic copper interface layer is too large, it will increase the interface impedance, reduce the cycle performance of the battery, and also reduce the energy density of the battery.
[0017] Preferably, the copper layer is prepared by magnetron sputtering.
[0018] Preferably, the thickness of the copper layer is 0.5μm to 3μm, for example, it can be 0.5μm, 0.7μm, 1μm, 1.2μm, 1.5μm, 1.8μm, 2μm, 2.3μm, 2.6μm, 2.8μm or 3μm, etc.
[0019] Preferably, the polymer base film is selected from at least one of polyethylene terephthalate film, polyimide film, or polypropylene film.
[0020] Preferably, the thickness of the polymer base film is 3μm to 8μm, for example, it can be 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm or 8μm, etc.
[0021] In a second aspect, the present invention provides a method for preparing a current collector as described in the first aspect, comprising the following steps:
[0022] (1) Provide a polymer film with a copper layer on its surface as a pre-formed current collector;
[0023] (2) Prepare an electrochemical displacement deposition solution, which includes copper salt, silver salt and acid. Immerse the pre-prepared current collector into the electrochemical displacement deposition solution to carry out an electrochemical reaction and obtain the current collector.
[0024] This invention utilizes a combined electrochemical displacement-autocatalytic deposition method to prepare a three-dimensional porous dendritic copper interface layer. During the electrochemical reaction, silver ions in the deposition solution undergo a displacement reaction with the copper layer on the surface of the pre-formed current collector (equation: Cu + 2Ag). + =2Ag+Cu 2+ The formation of silver nanoparticles, which act as heterogeneous nucleation sites, induces Cu in the deposition solution. 2+ The silver nanoparticles are grown by self-catalytic reduction, and a three-dimensional porous dendritic copper interface layer is eventually constructed in situ on the copper layer surface, forming an integrated multi-level functional interface that is both conductive and anchored, which can adapt to the loading and bonding of silicon-based anode active materials.
[0025] The method of the present invention can be carried out at room temperature (20℃~30℃), the reaction conditions are mild and the reaction is rapid, the preparation process is simple, no complex equipment is required, it is easy to integrate into the post-processing stage of existing composite copper foil production, the additional cost is extremely low, and it is suitable for the industrial application of silicon-based anodes for lithium-ion batteries.
[0026] Preferably, the preparation method of the pre-formed current collector in step (1) includes: providing a polymer base film, and preparing a copper layer on the surface of the polymer base film by magnetron sputtering to obtain the pre-formed current collector. In this method, a continuous, pore-free, dense copper layer can be formed by magnetron sputtering, providing the current collector with high in-plane conductivity and ensuring rapid electron transport.
[0027] Preferably, the method further includes surface treatment of the pre-formed current collector, the surface treatment including at least one of surface cleaning, micro-etching roughening and activation treatment.
[0028] Surface cleaning includes immersing the pre-made current collector in an alkaline solution and ultrasonic treatment.
[0029] Micro-etching roughening includes placing a pre-made current collector in a micro-etching solution.
[0030] The activation process includes placing the pre-made current collector in an acidic solution.
[0031] In this preferred technical solution, surface cleaning can remove surface oil, adsorbed impurities and organic residues; micro-etching roughening can construct a micron-level uneven rough structure on the copper layer surface, which is beneficial for the preparation of a three-dimensional porous dendritic copper interface layer; and activation treatment can remove the oxide layer on the copper layer surface.
[0032] Preferably, in the micro-etching roughening step, the micro-etching solution includes acid, oxidant and water.
[0033] Preferably, the acid in the micro-etching solution includes at least one of sulfuric acid, methanesulfonic acid, and phosphoric acid.
[0034] Preferably, the acid volume concentration in the micro-etching solution is 50 mL / L to 150 mL / L, for example, 50 mL / L, 60 mL / L, 70 mL / L, 80 mL / L, 100 mL / L, 110 mL / L, 120 mL / L, 130 mL / L, or 150 mL / L; the hydrogen peroxide volume concentration is 10 mL / L to 50 mL / L, for example, 10 mL / L, 20 mL / L, 30 mL / L, 40 mL / L, or 50 mL / L. If the acid volume concentration is too low, it will lead to insufficient micro-etching; if the acid volume concentration is too high, it will lead to over-etching of the copper layer later.
[0035] Preferably, the oxidant includes at least one of hydrogen peroxide, sodium persulfate, and potassium persulfate.
[0036] Preferably, the volume concentration of hydrogen peroxide in the micro-etching solution is 10 mL / L to 50 mL / L, for example, it can be 10 mL / L, 15 mL / L, 20 mL / L, 25 mL / L, 30 mL / L, 35 mL / L, 40 mL / L, 45 mL / L or 50 mL / L, etc.
[0037] Preferably, the mass concentration of sodium persulfate and / or potassium persulfate in the micro-etching solution is 50 g / L to 110 g / L, for example, it can be 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L or 110 g / L, etc.
[0038] In this invention, if the concentration of the oxidant is too low, the roughening effect will be insufficient; if the concentration of the oxidant is too high, it will accelerate the decomposition of the reagent and damage to the copper layer.
[0039] Preferably, the micro-etching solution also includes a hydrogen peroxide stabilizer, which includes ethanol and / or benzotriazole. The concentration of the hydrogen peroxide stabilizer in the micro-etching solution is 5 ppm to 50 ppm, for example, it can be 5 ppm, 10 ppm, 15 ppm, 20 ppm, 25 ppm, 30 ppm, 35 ppm, 40 ppm, 45 ppm or 50 ppm, etc.
[0040] Preferably, the micro-etching and coarsening time is 15s to 60s, for example, it can be 15s, 20s, 25s, 30s, 35s, 40s, 45s, 50s, 55s or 60s.
[0041] Preferably, the temperature for micro-etching and roughening is 20℃~35℃, for example, it can be 20℃, 22℃, 23℃, 25℃, 27℃, 30℃, 32℃, 34℃ or 35℃, etc.
[0042] Preferably, the surface roughness Ra of the current collector after micro-etching is 0.5 μm to 1 μm. If the roughness is too small, the bonding force between the current collector and the negative electrode active layer will be too weak; if the roughness is too large, it will increase the interfacial impedance and reduce the cycle performance of the battery.
[0043] Preferably, the weight loss rate of the current collector after micro-etching roughening is 5% to 8% compared to the current collector before micro-etching roughening, for example, it can be 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, or 8%. If the weight loss rate is less than 5%, the micro-etching is insufficient, the surface roughness of the copper foil is low, the oxide layer on the copper surface remains, which easily leads to sparse dendrite growth, weak interfacial bonding, and easy coating peeling. If the weight loss rate is greater than 8%, the micro-etching is excessive, the thickness of the dense copper layer is uneven, and pinholes and defects are easily generated, which reduces the conductivity and mechanical flexibility. At the same time, the surface trenches are too deep, causing dendrite agglomeration and deformity, partial failure of the pore structure, and poor cycle stability.
[0044] In one embodiment, the prefabricated current collector is subjected to surface cleaning, micro-etching roughening, and activation treatment in sequence.
[0045] In one embodiment, the surface-treated pre-formed current collector is washed with water and dried to obtain a pre-formed current collector with a clean surface, no oxidation, and excellent activity.
[0046] In one embodiment, nitrogen gas is used for drying, and the drying is carried out at a wind speed of 0.5 m / s to 1 m / s.
[0047] Preferably, the copper salt includes at least one of copper sulfate, copper chloride, and copper nitrate.
[0048] Preferably, the concentration of copper salt in the electrochemical displacement deposition solution is 0.05 mol / L to 0.2 mol / L, for example, it can be 0.05 mol / L, 0.07 mol / L, 0.1 mol / L, 0.12 mol / L, 0.15 mol / L, 0.17 mol / L, or 0.2 mol / L, etc. More preferably, it is 0.08 mol / L to 0.15 mol / L.
[0049] Preferably, the silver salt includes at least one of silver nitrate and silver sulfate.
[0050] Preferably, the concentration of silver salt in the electrochemical displacement deposition solution is 0.001 mol / L to 0.01 mol / L, for example, it can be 0.001 mol / L, 0.002 mol / L, 0.003 mol / L, 0.004 mol / L, 0.005 mol / L, 0.006 mol / L, 0.007 mol / L, 0.008 mol / L, 0.009 mol / L, or 0.01 mol / L, etc. Preferably, it is 0.003 mol / L to 0.008 mol / L.
[0051] Preferably, the acid includes at least one of sulfuric acid and hydrochloric acid.
[0052] Preferably, the concentration of acid in the electrochemical displacement deposition solution is 0.5 mol / L to 1.0 mol / L, for example, it can be 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L or 1.0 mol / L, etc.
[0053] Preferably, the electrochemical displacement deposition solution also includes a morphology modifier, which preferably includes at least one of polyethylene glycol, gelatin, and thiourea.
[0054] Preferably, the concentration of the morphology modifier is 10ppm to 50ppm, based on the total mass of the electrochemically replaced deposition solution, for example, it can be 10ppm, 15ppm, 20ppm, 25ppm, 30ppm, 35ppm, 40ppm, 45ppm or 50ppm, etc.
[0055] Preferably, the temperature of the electrochemical reaction is 20℃~30℃, for example, it can be 20℃, 22℃, 24℃, 26℃, 28℃ or 30℃, etc.
[0056] Preferably, the electrochemical reaction is carried out under light-protected and unstirred conditions. This is because the silver salts in the deposition solution are extremely sensitive to light. Under light, silver ions (Ag⁺) rapidly undergo photodecomposition, being reduced to black elemental silver (Ag), leading to premature consumption of silver ions, affecting dendrite growth, and causing the plating solution to become cloudy and ineffective. Stirring inhibits dendrite formation; in a static state, copper atoms spontaneously form a three-dimensional dendritic structure.
[0057] Preferably, the electrochemical reaction time is 30s to 300s, for example, it can be 30s, 40s, 50s, 60s, 70s, 80s, 90s, 100s, 110s, 120s, 130s, 140s, 150s, 160s, 170s, 180s, 190s, 200s, 210s, 220s, 230s, 240s, 250s, 260s, 270s, 280s, 290s, or 300s, etc., and preferably 90s to 180s.
[0058] In one embodiment, the current collector obtained after the electrochemical reaction is post-treated, including cleaning and drying.
[0059] In one embodiment, the cleaning method is as follows: the current collector obtained after the reaction is taken out from the sediment and rinsed repeatedly with deionized water at a low flow rate 2 to 5 times, each time for 2 to 5 minutes, to thoroughly remove the sediment and reaction byproducts remaining on the surface.
[0060] In one embodiment, the low flow rate is 5 mL / min to 10 mL / min, for example, it can be 5 mL / min, 6 mL / min, 7 mL / min, 8 mL / min, 9 mL / min or 10 mL / min, etc.
[0061] In one embodiment, the drying method is as follows: the cleaned current collector is placed in a vacuum drying oven, heated to 70°C~90°C, dried under vacuum for 15min~45min, and then cooled to room temperature to obtain the finished current collector.
[0062] Thirdly, the present invention provides a negative electrode sheet, the negative electrode sheet comprising a current collector and a silicon-based active layer disposed on the surface of the current collector, wherein the current collector is a current collector of the first aspect or a current collector prepared by the method of the second aspect.
[0063] The use of the current collector of the present invention to prepare silicon-based anode sheets can effectively increase the bonding force between the silicon-based active layer and the current collector, alleviate the volume expansion of the silicon-based active material, and reduce the interfacial impedance.
[0064] Fourthly, the present invention provides a lithium-ion battery, which includes the negative electrode sheet of the third aspect.
[0065] The lithium-ion battery of the present invention has the advantages of high capacity, good cycle performance and good high-rate charge and discharge performance.
[0066] The numerical range of this invention includes not only the point values listed above, but also any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values included in the range.
[0067] Compared with existing technologies, the present invention has the following beneficial effects:
[0068] (1) In the current collector of the present invention, the polymer base film provides basic support and excellent flexibility for the copper layer, which can be adapted to the winding and rolling process of lithium-ion batteries. The copper layer can provide good electron transport for the current collector. The dendritic structure in the three-dimensional porous dendritic copper interface layer is like countless "micro-hooks" embedded in the negative electrode active layer, which transforms the traditional surface-to-surface contact into a three-dimensional interlocking connection, which can increase the bonding strength between the current collector and the silicon-based active layer; the pores between the dendrites can effectively absorb the volume expansion stress of the negative electrode active material, reduce the generation of cracks in the negative electrode active layer, and help improve cycle performance; the three-dimensional porous dendritic copper interface layer has a huge specific surface area, which can significantly reduce the interface charge transfer impedance, which is beneficial to high-rate charge and discharge performance.
[0069] (2) The peel strength of the silicon-carbon anode made by the current collector of the present invention is 10.3 N / m or more, preferably 13.8 N / m or more, and even more preferably 32.1 N / m or more; the battery made by the current collector of the present invention has the advantages of low interfacial charge resistance, good cycle performance and good rate performance, with an interfacial charge transfer resistance of 86 Ω or less, preferably 70 Ω or less, and even more preferably 46 Ω or less; a capacity retention rate of 68.1% or more after 200 cycles, preferably 69.3% or more, and even more preferably 83.5% or more; and a rate performance of 68% or more, preferably 72% or more, and even more preferably 84% or more. Detailed Implementation
[0070] The technical solution of the present invention will be further illustrated below through specific embodiments.
[0071] The specific embodiments described herein are for illustrative purposes only and are not intended to limit the scope of the invention.
[0072] In the specific implementation, all operations without specified conditions are performed at room temperature (25±5℃) and normal pressure.
[0073] Example 1
[0074] This embodiment provides a current collector, including a polymer base film, a dense copper layer, and a three-dimensional porous dendritic copper interface layer (hereinafter referred to as the dendritic layer). The dense copper layer is formed on both sides of the polymer base film, and the three-dimensional porous dendritic copper interface layer is formed on the surface of the dense copper layer.
[0075] The polymer base film is a polyethylene terephthalate (PET) film with a thickness of 5 μm.
[0076] The thickness of the dense copper layer on one side is 1.5 μm.
[0077] The three-dimensional porous dendritic copper interface layer includes a multi-level structure composed of dendritic copper crystals, which include dendritic trunks and dendritic branches growing on the dendritic trunks. The average diameter of the dendritic trunks is 250 nm, the length of the dendritic branches is 2.8 μm, and the angle between the dendritic trunks and dendritic branches is in the range of 30° to 60°. The average thickness of the three-dimensional porous dendritic copper interface layer is 3.5 μm, and the average porosity of the three-dimensional porous dendritic copper interface layer is 65%.
[0078] This embodiment also provides a method for preparing the above-mentioned current collector, including the following steps:
[0079] Step 1: Prepare the prefabricated manifold.
[0080] A 5μm thick PET film was selected as the base film, and a dense copper layer was deposited on both sides of it by magnetron sputtering to form a copper-clad base film, which was used as a pre-fabricated current collector. The magnetron sputtering parameters were: copper target purity 99.99%, argon pressure 0.3Pa, sputtering power 300W, deposition rate 5nm / s, and substrate temperature 60℃.
[0081] Step 2: The prefabricated current collector undergoes surface treatment in sequence.
[0082] Surface treatment includes sequential degreasing and cleaning, micro-etching and roughening, and acid pickling and activation treatment, specifically:
[0083] The degreasing and cleaning method includes immersing the pre-made current collector in an alkaline degreasing solution at 60°C, ultrasonically cleaning for 10 minutes, and then rinsing with deionized water. The alkaline degreasing solution consists of: 50 g / L sodium hydroxide, 30 g / L sodium carbonate, 20 g / L trisodium phosphate, with the remainder being deionized water.
[0084] The micro-etching roughening method includes: transferring the pre-fabricated current collector after degreasing and cleaning to a micro-etching solution at room temperature and treating it for 30 seconds. The composition of the micro-etching solution is: 100 mL / L sulfuric acid, 30 mL / L hydrogen peroxide, and the balance being deionized water. The copper layer weight loss rate is controlled at 6%, and the surface Ra of the pre-fabricated current collector after micro-etching roughening is 0.7 μm.
[0085] The pickling and activation treatment method includes: placing the pre-made current collector after micro-etching and roughening into the pickling solution and pickling and activating it for 20 seconds. The pickling solution is a solution of 5% hydrochloric acid and deionized water mixed at a volume ratio of 1:19.
[0086] After the pickling and activation treatment is completed, the pre-formed current collector is rinsed with deionized water until neutral, and then dried with nitrogen (wind speed 0.8m / s) to obtain the surface-treated pre-formed current collector.
[0087] Step 3: Constructing a three-dimensional porous dendritic copper interface layer
[0088] The surface-treated pre-made current collector was immersed in an electrochemical displacement deposition solution, which consisted of 0.1 mol / L copper sulfate, 0.005 mol / L silver nitrate, 0.8 mol / L sulfuric acid, and 30 ppm polyethylene glycol (PEG-2000) (based on the total mass of the deposition solution). The reaction was allowed to proceed for 120 s under light-proof and unstirred conditions, resulting in the in-situ growth of a three-dimensional porous dendritic copper interface layer on the surface of the dense copper layer, thus obtaining the current collector.
[0089] Step 4: Post-processing
[0090] The current collector was removed from the electrochemical displacement deposition solution and rinsed three times with deionized water at a flow rate of 8 mL / min for 2 min each time. Then it was placed in a vacuum drying oven and heated to 80 °C at a rate of 5 °C / min. It was dried under a vacuum of -0.09 MPa for 30 min and cooled to room temperature to obtain the finished current collector.
[0091] Example 2
[0092] The difference between this embodiment and Embodiment 1 is that a polypropylene (PP) film with a thickness of 5 μm is used as the base film, while the rest of the preparation methods and parameters are the same as in Embodiment 1.
[0093] Example 3
[0094] The difference between this embodiment and Example 1 is that, in step three, the concentration of silver nitrate in the precipitation solution is 0.001 mol / L. The remaining preparation methods and parameters are the same as in Example 1.
[0095] In this embodiment, the average thickness of the three-dimensional porous dendritic copper interface layer in the current collector is 1.8 μm.
[0096] Example 4
[0097] The difference between this embodiment and Example 1 is that, in step three, the concentration of silver nitrate in the precipitation solution is 0.01 mol / L. The remaining preparation methods and parameters are the same as in Example 1.
[0098] In the current collector of this embodiment, the average thickness of the three-dimensional porous dendritic copper interface layer is 6.2 μm.
[0099] Example 5
[0100] The difference between this embodiment and Example 1 is that in step three, the reaction time is 30 seconds. The remaining preparation methods and parameters are the same as in Example 1.
[0101] In the current collector of this embodiment, the average thickness of the three-dimensional porous dendritic copper interface layer is 0.8 μm.
[0102] Example 6
[0103] The difference between this embodiment and Example 1 is that in step three, the reaction time is 300 seconds. The remaining preparation methods and parameters are the same as in Example 1.
[0104] In this embodiment, the average thickness of the three-dimensional porous dendritic copper interface layer in the current collector is 10.3 μm.
[0105] Example 7
[0106] The difference between this embodiment and Embodiment 1 is that micro-etching and roughening were not performed in step two. The remaining preparation methods and parameters are the same as in Embodiment 1.
[0107] In the current collector of this embodiment, the average thickness of the three-dimensional porous dendritic copper interface layer is 2.9 μm.
[0108] Example 8
[0109] The difference between this embodiment and Example 1 is that, in step three, the deposition solution does not contain polyethylene glycol. The remaining preparation methods and parameters are the same as in Example 1.
[0110] Example 9
[0111] The difference between this embodiment and Example 1 is that, in step three, the concentration of copper sulfate in the precipitation solution is 0.06 mol / L. The remaining preparation methods and parameters are the same as in Example 1.
[0112] In the current collector of this embodiment, the average thickness of the three-dimensional porous dendritic copper interface layer is 1.2 μm.
[0113] Example 10
[0114] The difference between this embodiment and Example 1 is that, in step three, the concentration of copper sulfate in the precipitate is 0.2 mol / L. The remaining preparation methods and parameters are the same as in Example 1.
[0115] Comparative Example 1
[0116] The current collector in this comparative example is the substrate in Example 1, namely a 5μm thick PET film.
[0117] Comparative Example 2
[0118] The difference between this comparative example and Example 1 is that, in step three, the deposition solution does not contain silver nitrate. The remaining preparation methods and parameters are the same as in Example 1.
[0119] The presence and parameters of a three-dimensional porous dendritic copper interface layer in the current collectors of Examples 1-10 and Comparative Examples 1-2 were detected, and the results are shown in Table 1.
[0120]
[0121] As shown in Table 1, the method of the present invention can form a three-dimensional porous dendritic copper interface layer in the current collector. In contrast, the preparation method of Comparative Example 2 cannot form a three-dimensional porous dendritic copper interface layer because it does not contain silver salt.
[0122] Battery fabrication:
[0123] Using the current collectors from Examples 1-10 and Comparative Examples 1-2 as negative electrode current collectors, silicon-carbon negative electrodes were prepared. The silicon-carbon negative electrode includes a negative electrode current collector and a silicon-based active layer disposed on its surface. The Si content in the silicon-based active layer is 20 wt%, and the compaction density of the silicon-carbon negative electrode is 1.4 g / cm³. 3 A CR2032 coin cell was assembled in an argon glove box (with water and oxygen content both <0.1ppm) using lithium metal sheets as the counter electrode, Celgard 2400 as the separator, and 1mol / L LiPF6 as the electrolyte (a mixture of EC and DMC in a 1:1 volume ratio).
[0124] Electrode testing:
[0125] According to GB / T2792-2014, the silicon-carbon anode was tested to obtain the peel strength between the current collector and the silicon-based active layer.
[0126] Battery test:
[0127] (1) Before cycling, the charge transfer impedance (Rct) of the coin cell was tested. The test method was electrochemical impedance spectroscopy (EIS) test, and the test conditions were: frequency range 100kHz-0.01Hz, amplitude 5mV.
[0128] (2) Maintain a constant temperature of 25℃, a voltage window of 0.01~1.5V, and a charge / discharge rate of 0.5C for 200 cycles. Record the initial discharge specific capacity and the discharge specific capacity per cycle. Based on the initial discharge capacity C1 and the discharge capacity of the 200th cycle C... 200 Based on this, the capacity retention rate after 200 cycles is calculated using the following formula: C 200 / C1×100%.
[0129] (3) At a constant temperature of 25℃, with a charging rate of 2C and a fixed discharge rate of 0.2C, calculate the 2C / 0.2C capacity ratio to test the rate performance.
[0130] The test results are shown in Table 2.
[0131]
[0132] As can be seen from the table above, there is basically no difference in performance between Example 2 and Example 1, indicating that the method of the present invention has good universality for different polymer base films.
[0133] Compared to Example 1, in Example 3, the silver nitrate concentration in the deposition solution was reduced to 0.001 mol / L, the average thickness of the dendrite layer decreased to 1.8 μm, the peel strength was only 22.4 N / m, and the capacity retention rate after 200 cycles was 74.2%. In Example 4, the silver nitrate concentration in the deposition solution was increased to 0.01 mol / L, the average thickness of the dendrite layer increased to 6.2 μm, and the porosity increased to 71%, but the dendrite trunks were large (average diameter 380 nm), and the cycle retention rate decreased to 79.5%. This indicates that controlling the AgNO3 concentration within the range of 0.003 mol / L to 0.008 mol / L is more conducive to improving battery performance.
[0134] Compared to Example 1, Example 5 had a resting reaction time of 30 s, resulting in an average dendrite layer thickness of only 0.8 μm, a peel strength of 13.8 N / m, and a capacity retention rate of 69.3% after 200 cycles, close to the comparative example level. Example 6 had a resting reaction time of 300 s, resulting in an average dendrite layer thickness of 10.3 μm. Although the peel strength increased to 36.2 N / m, the capacity retention rate after 200 cycles decreased to 74.8%, and the interfacial impedance rebounded to 58 Ω. This indicates that controlling the reaction time within the range of 90 s to 180 s is more conducive to improving battery performance.
[0135] Compared to Example 1, Example 7 omitted the micro-etching roughening process, the average thickness of the dendrite layer was reduced to 2.9 μm and the distribution was uneven, the peel strength was reduced to 24.5 N / m, and the capacity retention rate after 200 cycles was 76.8%, all of which were significantly lower than those in Example 1. This shows that the micro-etching roughening step has an important impact on improving the performance of the current collector.
[0136] Compared to Example 1, the deposition solution in Example 8 did not contain polyethylene glycol. The dendrite trunk thickened to an average diameter of 350 nm, the branch length increased to 3.2 μm, the peel strength was 28.9 N / m, and the cycle retention rate was 80.2%, which was slightly lower than that in Example 1. This indicates that adding morphology modifiers can refine the dendrite structure and improve interface stability.
[0137] Compared to Example 1, the copper sulfate concentration in the deposition solution of Example 9 was 0.06 mol / L, lower than the 0.1 mol / L concentration in Example 1. This lower concentration resulted in an average dendritic layer thickness of only 1.2 μm, a peel strength of 19.6 N / m, and a capacity retention rate of 70.5% after 200 cycles. In Example 10, the copper sulfate concentration in the deposition solution was 0.2 mol / L, higher than the 0.1 mol / L concentration in Example 1. This higher concentration led to loose deposition, a peel strength of only 10.3 N / m, and an interfacial impedance increasing to 86 Ω, even worse than the comparative example. This indicates that controlling the copper sulfate concentration within the range of 0.08 mol / L to 0.15 mol / L is more beneficial for improving battery performance.
[0138] Comparative Example 1 (smooth copper foil) exhibited a peel strength of 11.2 N / m, a capacity retention of 69.2% after 200 cycles, and an interfacial impedance of 82 Ω. Comparative Example 2 (deposition solution lacking AgNO3, thus preventing dendritic structure formation) showed performance essentially equivalent to Comparative Example 1, indicating that simply increasing the copper layer thickness does not improve interfacial adhesion.
[0139] The applicant declares that the detailed method of the present invention is illustrated by the above embodiments, but the present invention is not limited to the above detailed method, that is, it does not mean that the present invention must rely on the above detailed method to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A current collector, characterized in that, The current collector includes: Polymer-based film; A copper layer is formed on at least one side surface of the polymer-based film; A three-dimensional porous dendritic copper interface layer is formed on the surface of the copper layer.
2. The current collector according to claim 1, characterized in that, The average porosity of the three-dimensional porous dendritic copper interface layer is 50%~75%, preferably 55%~65%; Preferably, the three-dimensional porous dendritic copper interface layer includes a multi-level structure composed of dendritic copper crystals, wherein the dendritic copper crystals include a dendritic trunk and dendritic branches growing on the dendritic trunk, the average diameter of the dendritic trunk is 100nm~500nm, the length of the dendritic branches is 1μm~5μm, and the angle between the dendritic trunk and the dendritic branches is 30°~60°. Preferably, the average thickness of the three-dimensional porous dendritic copper interface layer is 1μm to 10μm, and more preferably 2μm to 6μm.
3. The current collector according to claim 1 or 2, characterized in that, The copper layer was prepared by magnetron sputtering. Preferably, the thickness of the copper layer is 0.5 μm to 3 μm; Preferably, the polymer-based film is selected from at least one of polyethylene terephthalate film, polyimide film, or polypropylene film; Preferably, the thickness of the polymer base film is 3μm to 8μm.
4. A method for preparing a current collector as described in any one of claims 1-3, characterized in that, The preparation method includes the following steps: (1) Provide a polymer film with a copper layer on its surface as a pre-formed current collector; (2) Prepare an electrochemical displacement deposition solution, wherein the electrochemical displacement deposition solution includes copper salt, silver salt and acid, and immerse the pre-made current collector in the electrochemical displacement deposition solution to carry out an electrochemical reaction to obtain the current collector.
5. The method for preparing a current collector according to claim 4, characterized in that, The preparation method of the pre-fabricated current collector in step (1) includes: providing a polymer base film, preparing a copper layer on the surface of the polymer base film by magnetron sputtering, and obtaining the pre-fabricated current collector.
6. The method for preparing the current collector according to claim 4 or 5, characterized in that, The method further includes surface treatment of the prefabricated current collector, the surface treatment including at least one of surface cleaning, micro-etching roughening and activation treatment; The surface cleaning includes: immersing the pre-made current collector in an alkaline solution and then ultrasonically treating it; The micro-etching roughening includes: placing the pre-made current collector in a micro-etching solution; The activation process includes placing the pre-made current collector in an acidic solution.
7. The method for preparing a current collector according to claim 6, characterized in that, In the micro-etching roughening step, the micro-etching solution includes acid, oxidant and water; Preferably, the acid in the micro-etching solution includes at least one of sulfuric acid, methanesulfonic acid, and phosphoric acid; Preferably, the volume concentration of acid in the micro-etching solution is 50 mL / L to 150 mL / L; Preferably, the oxidant includes at least one of hydrogen peroxide, sodium persulfate, and potassium persulfate; Preferably, the volume concentration of hydrogen peroxide in the micro-etching solution is 10 mL / L to 50 mL / L; Preferably, the mass concentration of sodium persulfate and / or potassium persulfate in the micro-etching solution is 50 g / L to 110 g / L; Preferably, the micro-etching solution further includes a hydrogen peroxide stabilizer, which includes ethanol and / or benzotriazole, and the concentration of the hydrogen peroxide stabilizer in the micro-etching solution is 5 ppm to 50 ppm. Preferably, the micro-etching and roughening time is 15s to 60s; Preferably, the temperature for micro-etching and roughening is 20℃~35℃; Preferably, the surface roughness Ra of the current collector after micro-etching is 0.5 μm to 1 μm; Preferably, the weight loss rate of the current collector after micro-etching and roughening is 5% to 8% compared to the current collector before micro-etching and roughening.
8. The method for preparing a current collector according to any one of claims 4-7, characterized in that, The copper salt includes at least one of copper sulfate, copper chloride, and copper nitrate; Preferably, the concentration of copper salt in the electrochemical displacement deposition solution is 0.05 mol / L to 0.2 mol / L, and more preferably 0.08 mol / L to 0.15 mol / L; Preferably, the silver salt includes at least one of silver nitrate and silver sulfate; Preferably, the concentration of silver salt in the electrochemical displacement deposition solution is 0.001 mol / L to 0.01 mol / L, more preferably 0.003 mol / L to 0.008 mol / L; Preferably, the acid includes at least one of sulfuric acid and hydrochloric acid; Preferably, the concentration of acid in the electrochemical displacement deposition solution is 0.5 mol / L to 1.0 mol / L; Preferably, the electrochemical displacement deposition solution further includes a morphology modifier, which preferably includes at least one of polyethylene glycol, gelatin, and thiourea. Preferably, the concentration of the morphology modifier is 10 ppm to 50 ppm, based on the total mass of the electrochemical displacement deposition solution. Preferably, the temperature of the electrochemical reaction is 20°C to 30°C; Preferably, the electrochemical reaction is carried out under light-protected and unstirred conditions; Preferably, the electrochemical reaction takes 30s to 300s, and more preferably 90s to 180s.
9. A negative electrode sheet, characterized in that, The negative electrode includes a current collector and a silicon-based active layer disposed on the surface of the current collector. The current collector is the current collector according to any one of claims 1-3, or the current collector prepared by any one of claims 4-8.
10. A lithium-ion battery, characterized in that, The lithium-ion battery includes the negative electrode sheet as described in claim 9.